Answer:
35340
Step-by-step explanation:
please like my answer
Answer: 35340
Step-by-step explanation: just multiply
Answer:
Step-by-step explanation:
(0, 4) (2, 0)
(0-4)/(2-0) = -4/2 = -2
y - 4 = -2(x - 0)
y - 4 = -2x + 0
y = -2x + 4
Please help
2. Consider the following line plot.
2
4
6
8
(a) What is the general trend of the graph?
(b) What is the median of the data? Explain.
(c) What is the mean of the data? Explain. Round to the Nearest tenth.
(d) Would the mean or median be affected more with a data point of 20? Explain.
Answer:
P
Answer:
BUDDY PUT THE WHOLE TEST ON HERE
Step-by-step explanation:
Answer:
4. is x = 9
but I don't know about 5. sorry.
Step-by-step explanation:
5x + 3 = 48
-3. -3
5x = 45
5. 5
x = 9
5(9) + 3 = 48
48 = 48
The peregrine falcon flies in the time it takes the eagle to fly 40 miles is 64 miles away.
The average speed is the total distance traveled by the object in a particular time interval.
The average speed is a scalar quantity.
The average speed of a golden eagle is 30 mph and the average speed of a peregrine falcon is 48 mph.
The time to fly 40 miles (that time is x):
miles hours
30 ⇒ 1
40 ⇒ x
We use the ruleof three which is to multiply the cross quantities on the table and divide by the remaining quantity:
x = 40(1)/30
x = 4/3 hour
it takes the eagle 4/3 flies to fly 40 miles.
Now we use the velocity of the falcon: 48mph, which can also be represented as:
miles hours
48 ⇒ 1
and we need the distance in miles that the falcon flies in 4/3 hours :
miles hours
48 ⇒ 1
x ⇒ 4/3
Again we use the rule of three (multiply cross quantities and divide by the remainingquantity)
x = (48)× (4/3)
x = 64 miles
Hence, the peregrine falcon flies in the time it takes the eagle to fly 40 miles is 64 miles away.
Learn more about average speed here;
#SPJ2
Answer:
64
Step-by-step explanation:
64 miles
Answer:
23 + b ≤ -276
Step-by-step explanation:
In this exercise, you're required to write an algebraic expression for the word problem. Thus, you'll write out a mathematical equation using the given values and unknown variable.
Translating the word problem into an algebraic expression, we have;
23 + b ≤ -276
Simplifying further, we have;
b ≤ -276 - 23
b ≤ -299